How to build a virtual personal imagined in the picture, directed by James Cameron (Avatar) movie as a model (Al-Academy, 2017)
The personal drama in particular, and one of the key elements underlying the dramatic structure to convey ideas and visions presented by the author when writing the text of the dramatic fall after that on the way out the submission form that suits the proposals of the text and processors directorial would push the wheel of dramatic structure to the front. So take the maker of the artwork (writer) undertook the transfer of those events and personalities in art presumed sometimes real and sometimes, in order to enrich the art inspired by the human reality through the ages, and full of its themes and ideas that led to the development experiences of peoples experiences of living. Therefore, we find it important to research in the characters dramatic, especially virtual ones, which is built-maker artwork artistic style, reflects the capacity of the writer's imagination and fertility of his ideas and what posed the impact in the hearts of the recipients, as a carrier of ideas and point of view of its maker, was full of movies many of the writers and authors who took the building and virtual personalities that do not resemble human beings, most notably the director (James Cameron), who is one of the industry pioneers and creators of virtual characters in the movie film, so we decided to stand on a cinematic experience in the film (Avatar). The Department of the researcher in this study, five chapters on the topic. Came the first chapter entitled systematic framework and included a research problem represented by the following question: What are the modalities used in character building in a virtual mock imagined by director James Cameron in the film (Avatar) model? The first chapter also included the importance of research and goals of the disclosure of modes that are built by default in the Personal Image imagined by director James Cameron in the film (Avatar). The second chapter has included a theoretical framework; the theoretical framework has been divided into three sections. First section: personal and personal default, were interested in studying personal drama and personal drama default, construction and do, and orientations and motivations. The second Section: Image and imaginary character building. Were interested in studying imagined the picture of the author and writer and director and the role of imagination in the character building. The third chapter dealt with the researcher measures that have been adopted in the analysis of the sample did not (Avatar) for the purpose of reaching a goal of the research. This included the chapter on research methodology and sample selection, and justification for the search tool. The fourth chapter has included an analysis of the selected Sample intentionality and extracts the desired results of the analysis. As he was the most prominent of the process of transformation in personal default of the hero came as a reaction against the attitudes of society, the real, and the adoption of these characters and the different ways to express her ideas (such as commentary on the event) technique in building a personal narrative. The researcher came out of the conclusions derived from the results of the analysis and the research contained some recommendations and suggestions that the researcher deems necessary for further studies included a list of research sources and summary of the research in English